Changes in low-molecular-weight thiol-disulphide redox couples are part of bread wheat seed germination and early seedling growth. (3rd June 2017) - Gerna, Davide; Roach, Thomas; Stöggl, Wolfgang; Wagner, Johanna; Vaccino, Patrizia; Limonta, Margherita; Kranner, Ilse
Abstract: The tripeptide antioxidant glutathione (γ-l -glutamyl-l -cysteinyl-glycine; GSH) essentially contributes to thiol-disulphide conversions, which are involved in the control of seed development, germination, and seedling establishment. However, the relative contribution of GSH metabolism in different seed structures is not fully understood. We studied the GSH/glutathione disulphide (GSSG) redox couple and associated low-molecular-weight (LMW) thiols and disulphides related to GSH metabolism in bread wheat ( Triticum aestivum L.) seeds, focussing on redox changes in the embryo and endosperm during germination. In dry seeds, GSH was the predominant LMW thiol and, 15 h after the onset of imbibition, embryos of non-germinated seeds contained 12 times more LMW thiols than the endosperm. In germinated seeds, the embryo contained 17 and 11 times more LMW thiols than the endosperm after 15 and 48 h, respectively. This resulted in the embryo having significantly more reducing half-cell reduction potentials of GSH/GSSG and cysteine (Cys)/cystine (CySS) redox couples (EGSSG/2GSH and ECySS/2Cys, respectively). Upon seed germination and early seedling growth, Cys and CySS concentrations significantly increased in both embryo and endosperm, progressively contributing to the cellular LMW thiol-disulphide redox environment (Ethiol-disulphide ). The changes in ECySS/2Cys could be related to the mobilisation of storage proteins in the endosperm during early seedling growth. We suggest that EGSSG/2GSH and ECySS/2Cys can be used as markers of the physiological and developmental stage of embryo and endosperm. We also present a model of interaction between LMW thiols and disulphides with hydrogen peroxide (H2 O2 ) in redox regulation of bread wheat germination and early seedling growth.